2020
DOI: 10.21303/2504-5695.2020.001201
|View full text |Cite
|
Sign up to set email alerts
|

Commodity Study of Developed Cupcakes of Organic Raw Materials

Abstract: For widening the assortment of floury confectionary products of organic raw materials, recipes of new cupcakes of sandy dough "Cosmic" and "Lunik" were offered. Reports on research projects (2020), «EUREKA: Life Sciences» Number 2 64 Food Science and Technology The recipe of cakes "Cosmic" included the organic raw materials: rice flour, grinded ginger, lemongrass powder, coconut sugar, creamy butter and sea buckthorn oil, mélange of chicken eggs, black ashberry jam. The recipe of cakes "Lunik" included rice fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…The data in Table 3 indicate that the content of toxic elements in organic cookies is lower than set by regulatory requirements. Studies [6][7][8] also found a lower content of heavy metal salts in products made from organic raw materials. Thus, we can conclude about the effectiveness of the use of organic raw materials to improve the safety of finished products.…”
Section: Discussion Of Results Of Studying the Devised Organic Cookiesmentioning
confidence: 96%
See 1 more Smart Citation
“…The data in Table 3 indicate that the content of toxic elements in organic cookies is lower than set by regulatory requirements. Studies [6][7][8] also found a lower content of heavy metal salts in products made from organic raw materials. Thus, we can conclude about the effectiveness of the use of organic raw materials to improve the safety of finished products.…”
Section: Discussion Of Results Of Studying the Devised Organic Cookiesmentioning
confidence: 96%
“…Despite a significant body of research into the biological value of organic agricultural produce, the range of organic flour products is still not wide enough. There are data regarding the development of new recipes for muffins [6], cookies [7], cakes [8], waffles [9] based on organic raw materials. The above studies prove that flour products developed from organic raw materials have high consumer properties.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%